1988
DOI: 10.1002/anie.198813551
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Routes to Di‐tert‐butylsilanediyl: Chemical, Thermal and Photochemical Generation

Abstract: 141 Crystal structure analysis of (Et4N),. 7 . C H X N (the values in brackets represent results of a structure determination on a second data set obtained from an independently grown new crystal): a = 16.557(!) [16.563(4)], b = 18.915(6) [18.879(6)], C = 17.110(6) [17.108(5)] A, a = / f = y = 9 0 " ; space group, Pbcm, 2 = 4 , pCalcd=1.35 g cm-,, pl,hu,= 1.40 g cm-,, p=12.9 cm-', 2Q,,,=4O0 (MoKa, L=O.71069A); 2620 unique reflections; used in refinement with F~z > 3 u ( F~) : 1290 [1376]; parameters 198. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 11 publications
3
74
0
1
Order By: Relevance
“…Strongly reducing conditions [Li(0) and t-Bu 2 SiCl 2 ] are needed to access the requisite lithium silylenoid (57). 67 Alternatively, free silylene 60 could be generated thermally or photochemically from cyclic silanes, such as 58 or 59. 12j,68-73 Each of these methods, however, limited the functionality that could be introduced on the silacyclopropane.…”
Section: Silacyclopropanes As Important Synthetic Intermediatesmentioning
confidence: 99%
“…Strongly reducing conditions [Li(0) and t-Bu 2 SiCl 2 ] are needed to access the requisite lithium silylenoid (57). 67 Alternatively, free silylene 60 could be generated thermally or photochemically from cyclic silanes, such as 58 or 59. 12j,68-73 Each of these methods, however, limited the functionality that could be introduced on the silacyclopropane.…”
Section: Silacyclopropanes As Important Synthetic Intermediatesmentioning
confidence: 99%
“…An important step forward was made by Boudjouk and coworkers when they found that bulky substituents (such as t-butyl) on silicon increased the stability of the silirane without preventing its thermolysis (equation 35) 56 . To explain the formation of the expected product of insertion into the H Si bond of HSiEt 3 in similar yields from different precursors, it was suggested that t-Bu 2 Si • • also arises by ultrasound-promoted lithio-dehalogenation of t-Bu 2 SiX 2 (X D Cl, Br, I); see also Section II.E.…”
Section: Pyrolysis Of Monosilanesmentioning
confidence: 99%
“…Another conceivable, but probably less likely, explanation of these experimental results 56 is that the triethylsilane somehow catalyzes the decomposition of silylenoid into free silylene, which can then insert into the Si H bond. In any case, the intermediacy of silylenes in˛-dehalogenations remains an open question, worthy of further study.…”
Section: E Silylenes From Metal-induced A-eliminationsmentioning
confidence: 99%
“…5,6 Since then people tried to detect, even to obtain some silylenoid species as well as to probe into their structures and properties. [7][8][9][10][11][12][13] However, as a kind of very reactive species, the preparation of silylenoids is very difficult. Until 1995, Tamao et al 14 reported the first experimental study of silylenoid chemistry, detected the existence of [(tert-butoxy)diphenylsilyl]lithium, Ph2SiLi(OBu-t), and investigated its chemical properties.…”
Section: Introductionmentioning
confidence: 99%